Use of Reconstruction Nail in The Treatment of Ipsilateral Femoral Neck and Shaft Fractures: Syed Kamran Ali Shah, Asif Peracha, Sajid Younus, Asmatullah Khan, Kazim Rahim Najjad, Muhammad Arsalan Ghazi (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To determine the effectiveness of ipsilateral femur- neck shaft fracture fixation with reconstruction nail at a tertiary health care centre.Methods: This was a prospective observational study conducted from April 2014 to March 2016. Twenty-seven Patients were registered using a predesigned proforma. Inclusion criteria were either gender with age between 18 â€“ 60 years with traumatic ipsilateral closed femur neck-shaft fracture. All patients registered subsequently underwent reconstruction nail insertion. The patients were followed in outpatient department after discharge at regular intervals to assess general recovery, complications and for assessment of fracture union. Results: All 27 patients achieved union of neck fracture in average duration of 127 days. All patients except one femur shaft fracture union achieved in mean duration of 250 days. 25 patients (i.e., 93%) had good functional status at the time of radiological union of shaft fracture while 2 (i.e., 7%) had fair functional status. None of the patients developed avascular necrosis of neck of femur and all the patients returned to their preinjury activity level and occupation.Conclusion: The current study suggests that reconstruction nail for the treatment of ipsilateral neck-shaft fracture of femur as a single implant produces acceptable clinical and functional outcomes if neck reduction is anatomically achieved. There is decreased blood loss with minimum soft tissue and periosteal disruption, which increases the possibility of fracture union. It is easier to address two fractures with single implant by reducing operating time and achieving possible high rate of radiological union with minimum risk of complications. Key Words: Reconstruction Nail, Ipsilateral femoral neck-shaft fracture, Compression Screw